Initial fast reaction of bromine on reovirus in turbulent flowing water. - Sharp, D G (1976)
An apparatus is described for precise observation of the kinetics of the initial fast reaction of bromine with reovirus in turbulent flowing water. When quantitative electron microscopy shows that virus suspensions are essentially all single particles, the loss of infectivity follows first-order kinetics, the plaque titer falling at the rate of 3 log10 units/s at pH 7, 2 C, and at a 3-muM bromine concentration. Virus suspensions containing small aggregates (2 to 10/clump) exhibit a constantly decreasing disinfection rate with bromine. At a survival level of 10(-3) for single virions, the aggregated preparations have lost only 99% of their plaque titer and 10(-4) is reached only after 4 s of exposure. The disinfection rate does not appear to be a simple function of the size and frequency of aggregates in the virus suspension even when the aggregates contain no foreign material. Unpurified virus preparations (crude freeze-thaw lysates of infected cells) are shown, by zonal centrifugation, to contain 50% to over 90% of the infectivity in large, fast sedimenting aggregates. Such aggregates would strongly influence the bromine resistance of virus in polluted water.